Upaya Penyelesaian Konflik Lahan Perkebunan PT. Bukit Barisan Indah Prima dengan Koperasi Unit Desa Harapan Baru di Kelurahan Simpang Tuan Kecamatan Mendahara Kabupaten Tanjung Jabung Timur - Maryati, Maryati; Rostarum, Triamy; Puspita, Sri Ayu Indah (Universitas Batanghari Jambi, 2024)
Conflict over plantation land is one of the plantation problems that cannot be resolved from time to time, which continues to make the community around the company anxious. Humans are categorized as individual creatures and as social creatures, inseparable from social relationships among other humans. This concerns each other's interests in interacting in society. As long as humans have different interests, conflict will always accompany them wherever they are. Conflict originates from a person's dissatisfaction with another person in terms of form or basic human needs (basic human needs), as stated, every human being has an interest in being able to have a desire to fulfill basic needs. For example, human material needs in the form of wealth can develop into needs for power, status and so on. As we all know, almost everyone has their own interests, both for themselves and their group. Differences in interests are one of the main factors that can trigger social conflict in society. One way of social conflict is the perception of differences in interests (perceived divergence of interest), or a belief that the aspirations of the conflicting parties cannot achieve the goals that have been agreed upon or achieved simultaneously. This means that the occurrence of a social conflict is caused by many factors so that the conflict is complex, involving various elements of society in it.